Anion-driven encapsulation of cationic guests inside pyridine[4]arene dimers - Kiesilä, Anniina; Moilanen, Jani O.; Kruve, Anneli; Schalley, Christoph A.; Barran, Perdita; Kalenius, Elina (Beilstein Journal of Organic Chemistry, 2019)
Pyridine[4]arenes have previously been considered as anion binding hosts due to the electron-poor nature of the pyridine ring. Herein, we demonstrate the encapsulation of Me4N+ cations inside a dimeric hydrogen-bonded pyridine[4]arene capsule, which contradicts with earlier assumptions. The complexation of a cationic guest inside the pyridine[4]arene dimer has been detected and studied by multiple gas-phase techniques, ESI-QTOF-MS, IRMPD, and DT-IMMS experiments, as well as DFT calculations. The comparison of classical resorcinarenes with pyridinearenes by MS and NMR experiments reveals clear differences in their host–guest chemistry and implies that cation encapsulation in pyridine[4]arene is an anion-driven process.
Keywords: cation binding; DFT calculations; ion mobility mass spectrometry; macrocycles; pyridinearenes; resorcinarenes

(untitled) - Timmerman, P.; Verboom, W.; Reinhoudt, D. N. (Tetrahedron, 1996)

(untitled) - Avram, L.; Cohen, Y. (J. Am. Chem. Soc., 2002)

(untitled) - Palmer, L. C.; Shivanyuk, A.; Yamanaka, M.; Rebek, J., Jr (Chem. Commun., 2005)

(untitled) - Gerkensmeier, T.; Mattay, J.; Näther, C. (Chem. – Eur. J., 2001)

(untitled) - Evan-Salem, T.; Cohen, Y. (Chem. – Eur. J., 2007)

(untitled) - Kiesilä, A.; Beyeh, N. K.; Moilanen, J. O.; Puttreddy, R.; Götz, S.; Rissanen, K.; Barran, P.; Lützen, A.; Kalenius, E. (Org. Biomol. Chem., 2019)

(untitled) - Letzel, M. C.; Decker, B.; Rozhenko, A. B.; Schoeller, W. W.; Mattay, J. (J. Am. Chem. Soc., 2004)

(untitled) - Rozhenko, A. B.; Schoeller, W. W.; Letzel, M. C.; Decker, B.; Mattay, J. (New J. Chem., 2013)

(untitled) - Schottel, B. L.; Chifotides, H. T.; Dunbar, K. R. (Chem. Soc. Rev., 2008)

(untitled) - Dawson, R. E.; Hennig, A.; Weimann, D. P.; Emery, D.; Ravikumar, V.; Montenegro, J.; Takeuchi, T.; Gabutti, S.; Mayor, M.; Mareda, J.; Schalley, C. A.; Matile, S. (Nat. Chem., 2010)

(untitled) - Kiesilä, A.; Kivijärvi, L.; Beyeh, N. K.; Moilanen, J. O.; Groessl, M.; Rothe, T.; Götz, S.; Topić, F.; Rissanen, K.; Lützen, A.; Kalenius, E. (Angew. Chem., Int. Ed., 2017)

(untitled) - Murayama, K. (Chem. Commun., 1998)

(untitled) - Mansikkamäki, H.; Nissinen, M.; Schalley, C. A.; Rissanen, K. (New J. Chem., 2003)

(untitled) - Mäkinen, M.; Vainiotalo, P.; Nissinen, M.; Rissanen, K. (J. Am. Soc. Mass Spectrom., 2003)

(untitled) - Kalenius, E.; Groessl, M.; Rissanen, K. (Nat. Rev. Chem., 2019)

(untitled) - Lee, T.-C.; Kalenius, E.; Lazar, A. I.; Assaf, K. I.; Kuhnert, N.; Grün, C. H.; Jänis, J.; Scherman, O. A.; Nau, W. M. (Nat. Chem., 2013)

(untitled) - Dearden, D. V.; Ferrell, T. A.; Asplund, M. C.; Zilch, L. W.; Julian, R. R.; Jarrold, M. F. (J. Phys. Chem. A, 2009)

(untitled) - Jurček, O.; Bonakdarzadeh, P.; Kalenius, E.; Linnanto, J. M.; Groessl, M.; Knochenmuss, R.; Ihalainen, J. A.; Rissanen, K. (Angew. Chem., Int. Ed., 2015)

(untitled) - Gabelica, V.; Shvartsburg, A. A.; Afonso, C.; Barran, P.; Benesch, J. L.; Bleiholder, C.; Bowers, M. T.; Bilbao, A.; Bush, M. F.; Campbell, J. L.; Campuzano, I. D.; Causon, T.; et al. (Mass Spectrom. Rev., 2019)

(untitled) - Larriba, C.; Hogan, C. J., Jr (J. Comput. Phys., 2013)

(untitled) - Larriba, C.; Hogan, C. J., Jr (J. Phys. Chem. A, 2013)

(untitled) - Beyeh, N. K.; Kogej, M.; Åhman, A.; Rissanen, K.; Schalley, C. A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Ernzerhof, M.; Scuseria, G. E. (J. Chem. Phys., 1999)

(untitled) - Adamo, C.; Barone, V. (J. Chem. Phys., 1999)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Grimme, S.; Antony, J.; Ehrlich, S.; Krieg, H. (J. Chem. Phys., 2010)

(untitled) - Grimme, S.; Ehrlich, S.; Goerigk, L. (J. Comput. Chem., 2011)

(untitled) - Hermann, J.; DiStasio, R. A., Jr; Tkatchenko, A. (Chem. Rev., 2017)

(untitled) - Ambrosetti, A.; Alfè, D.; DiStasio, R. A., Jr; Tkatchenko, A. (J. Phys. Chem. Lett., 2014)

(untitled) - Rao, L.; Ke, H.; Fu, G.; Xu, X.; Yan, Y. (J. Chem. Theory Comput., 2009)

(untitled) - Ireta, J.; Neugebauer, J.; Scheffler, M. (J. Phys. Chem. A, 2004)

(untitled) - Högberg, A. G. S. (J. Org. Chem., 1980)

(untitled) - Tunstad, L. M.; Tucker, J. A.; Dalcanale, E.; Weiser, J.; Bryant, J. A.; Sherman, J. C.; Helgeson, R. C.; Knobler, C. B.; Cram, D. J. (J. Org. Chem., 1989)